SOME ASPECTS OF THE BIOLOGY OF LACTARIUS LACTARIUS (SCHNEIDER) - Rao, T Appa (Indian Journal of Fisheries, 2011)
AMONG the lesser known fishes of India, the big-jawed jumper LactariuslaQfrnius^ .(Schn.) is a prized table fish. Sometimes when there areheavy- catches it is also cured. From Madras, Chid mb ram andy^nkataraman. (1946) and Devaresaii Â£ird Chidambaram (1953) gavebrief notes on the food of this species. Further Chacko (1949), Venkataraman-(I960) and Bas^eeruddin and Nayar (1961) mentioned the items.found in the stomach contents of this species from the coastal waters of Gulfof Mannar, Malabar and Madras respectively. The present paper deals-with the observations made by the author, on food and feeding habits,size at maturity, maturation and spawning, sex ratio, fecundity, growthand length-weight relationship of this spa;ies off Waltair during theperiod ' 1959-60.